1989
DOI: 10.1111/j.1365-2958.1989.tb00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the mini‐circle, a transposable element of Streptomyces coelicolor A3(2)

Abstract: The mini-circle is a transposable element which is present in Streptomyces coelicolor A3(2) in both free circular and chromosomally integrated linear forms. The nucleotide sequences of the mini-circle and its preferred site of integration in the Streptomyces lividans TK64 chromosome were determined. Three putative open reading frames were identified in the mini-circle sequence. The mini-circle does not appear to cause a target site duplication on transposition and does not have perfect terminal inverted repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…The lack of homology between these ORFs and other transposon-encoded products is not uncommon. The putative transposition-related proteins encoded by Streptomyces transposable elements, ISJJO (7), IS117 (20), and IS493 (35), also showed no homology to other known transposases.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of homology between these ORFs and other transposon-encoded products is not uncommon. The putative transposition-related proteins encoded by Streptomyces transposable elements, ISJJO (7), IS117 (20), and IS493 (35), also showed no homology to other known transposases.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that the sum of the sizes of the SspI fragments was very close to that for the other two enzymes was encouraging, but more extensive study would Construction and use ofAseI linking clones. Examination of the sequence of IS117, the S. coelicolor minicircle (35), revealed a single AseI site. Since there are two genetically mapped copies of IS117 integrated in the chromosome of S. coelicolor A3(2) (62), the cloned IS117 served as a linking clone for two pairs of genomic fragments generated byAseI.…”
Section: Methodsmentioning
confidence: 99%
“…Unusually, the insertion of IS116, IS900 or the mini-circle does not cause target site duplications ( Fig. 4; Green et al, 1989;Henderson et al, 1989) [the situation for IS110 is unclear because in the particular insertion event that was sequenced by Bruton & Chater (1987) the element had inserted into a run of seven C residues and was then flanked by runs of more than seven C residues]. The site into which IS116 is inserted in pIJ702 (CATGGTCGGTCTCCTGGT) corresponds closely to the consensus sequence CATG( N),-,CPyCCTT proposed as the target site for IS900 insertion, based on analysis of three insertion events ( Fig.…”
Section: Similarities and Diflerences Between The Ends And Target Sitmentioning
confidence: 99%
“…However, I S l l O (Chater et al, 1985;Bruton & Chater, 1987) and the 2.6 kb mini-circle (Lydiate et al, 1986;Henderson et al, 1989) from S. coelicolor and the recently discovered IS900 from Mycobacterium paratuberculosis (Green et al, 1989) have been found to form a 'family' of related elements based on similarity between amino acid sequences of their deduced gene products, despite the diversity of structure and host strains of these elements. The use of both IS110 and the mini-circle sequences to probe the DNA of a series of taxonomically varied streptomycetes revealed related elements in a minority of strains (Chater et al, 1985;Lydiate et al, 1986), but no hybridization to S. clavuligerus DNA.…”
Section: Introductionmentioning
confidence: 99%